Cysticercosis and neurocysticercosis in people from Mocuba district, Zambézia province: A Mozambican community-based study. - Janny Mucavele; Noémia Nhancupe; Gaby Ermelindo Roberto Monteiro; Regina Daniel Miambo; Lídia Gouveia; Alberto Pondja; Irina Mendes Sousa; Stephen W Bickler; Constance A Benson; Robert T Schooley; Veronika Schmidt; Charlotte Ruether; et al. (PLoS Neglected Tropical Diseases)
Introduction Taenia solium cysticercosis represents a significant public health concern, especially in low-income countries such as Mozambique, where especially the sub form neurocysticercosis can be associated with acute symptomatic seizures, epilepsy and other neurological and psychiatric disorders. Therefore, this study aimed to determine the prevalence of T. solium cysticercosis, neurocysticercosis, seizures and chronic headaches in the Mocuba district, Zambézia province, Mozambique, and to assess their associations. Methods The overall study combined both a community-based and a clinic-based segment, including epidemiological, clinical, laboratory and neuroradiological approaches, to investigate the prevalence and the association of cysticercosis, neurocysticercosis, seizure activity and chronic headaches in the Mocuba district. The community-based study involved 6,932 participants who were asked a questionnaire related to signs/symptoms of neurocysticercosis and who were asked to provide a blood sample for serological testing. Serological tests (Antigen-ELISA and Western blot) were used to detect cysticerci specific antigens and antibodies, respectively, in the participants. The clinic-based study included cerebral computed tomography (CT) of 233 individuals - a subset of those recruited from the community (with and without seizure activity and with and without cysticercosis based on serology). Results The prevalence of seizures and chronic headaches in the community-based study was 6.5% and 46.2% respectively, and the cysticercosis seroprevalence was 9.6%. Seizures and chronic headaches presented significant associations with cysticercosis seropositivity (p < 0.05). The clinic-based study revealed 9 (3.9%) of 233 individuals with neurocysticercosis-typical lesions on CT-scan of whom one case was negative on serology and on screening for seizure activity. Conclusions The community-based prevalence of seizure activity and cysticercosis was high in the Mocuba district. There was also a significant association of seizure activity and chronic headaches with the seroprevalence of cysticercosis and 8 out of 9 people with neurocysticercosis had seizure activity. This highlights the importance of increased awareness and the need for building health literacy within the healthcare workforce and the communities as well as the implementation of targeted interventions, both for people with seizure activity with and without neurocysticercosis. Future research should also assess the impact of preventive measures in reducing disease burden caused by T. solium.